Disaster Mitigation Communication Patterns: Case Studies in Natural Disaster Vulnerable Communities in Kulon Progo Regency - Rozak, Abdul; Mahfudz, Mochammad; Restendy, Mochammad Sinung; Sahlan, Mukhammad; Faiz, Achmad Zaky; Hakim, Lukman (Jurnal Komunikasi, 2023)
attention and vigilance. That's why disaster mitigation needs to be disseminated to all levels of society. One area that has a high level of vulnerability is Kulon Progo is a case study with a descriptive type in this research. Recorded in 2019 having 53 landslide-prone areas in 5 sub-districts. To anticipate victims, the Regional Disaster Management Agency (BPBD) of Kulon Progo Regency formed 3 Disaster Response Villages as bottom-up disaster mitigation pilots, one of which is Kalirejo Village. This effort is interesting in examining how communication patterns are carried out in natural disaster-prone areas (Kalirejo Village) in mitigating natural disasters. This study is qualitative and involves several elements including Kelurahan government officials, self-help groups, disaster risk reduction forums, volunteers, and residents who represent stakeholders related to mitigation. A qualitative approach is used to deepen understanding through observation, interviews, and focus group discussions. Data analysis uses an interactive model recommended by Miles and Huberman. The main findings of the study show that the most frequent natural disasters are landslides and floods. This is caused by the topography which causes unstable soil conditions so that it easily causes landslides when rainfall is high. The dominant communication pattern in terms of natural disaster management/mitigation is bottom-up, from the community to the Village, Kapanewon, and Regency Governments as well as BPBD. However, ritual communication patterns, both based on local traditions and wisdom as well as those with nuances of religious teachings, are still sustainable and ongoing.